(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the suitability of the dose distribution of vertebral growth plates in pediatric patients undergoing craniospinal radiotherapy with the recommendations of the SIOPE radiotherapy study group.Material and Methods: The study included 20 patients under the age of 12 who underwent 3-dimensional conformal craniospinal radiotherapy. For each patient, posterior and anterior primary ossification center of the cervical, thoracal, lumber and sacral vertebrae regions were re-contoured .The mean doses of each primary ossification center were determined and then the gradients were determined. The difference between the average doses of the anterior and posterior ossification centers of the vertebrae was evaluated separately for the cervical, thoracic, lumbar and sacral regions. Data were analyzed with descriptive statistics.Results: The mean doses of the posterior and anterior primary ossification center were respectively 23.62 Gy and 22.54 Gy for those lower than 25 Gy and 34.06 Gy and 33.09 Gy for those who underwent a dose greater than 25 Gy. The dose differences of the anterior and posterior ossification centers in the cervical, thoracal, lumbar and sacral vertebrae is lower than 5 Gy for those who underwent lower dose than 25 Gy.Conclusion: The planning data of craniospinal radiotherapy, which is applied to the cranial region with two lateral fields and the spinal area with single field, complies with the SIOPE recommendations.Primary and secondary ossification centers should be identified as the organ at risk for radiotherapy planning in the pediatric group undergoing craniospinal radiotherapy.Keywords: CSRT; vertebral primary ossification centers; radiotherapy dose distribution.